2019
DOI: 10.3389/fimmu.2019.00366
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the Absence of Nkx2-3 and MAdCAM-1 on the Distribution of Intestinal Type 3 Innate Lymphoid Cells and Postnatal SILT Formation in Mice

Abstract: Seeding of leukocytes to developing lymphoid tissues in embryonic and early postnatal age and to the mucosa throughout adulthood depends on the interaction between endothelial MAdCAM-1 addressin and its cognate ligand α4β7 integrin. Nkx2-3 as a transcriptional regulator of MAdCAM-1 controls vascular patterning in visceral lymphoid tissues in mice, and has been identified as a susceptibility factor for inflammatory bowel diseases in humans, associated with lymphoid neogenesis in the inflamed intestines. The rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In our previous study, we investigated the effect of the Nkx2-3 transcription factor (TF) genetic deficiency in autoimmune arthritis [ 26 ]. Nkx2-3 is a homeodomain TF which is crucial for the development of the spleen, and the expression and regulation of mucosal addressin cell adhesion molecule-1 (MADCAM-1) [ 28 , 29 ]. Nkx2-3 deficient mice (Nkx2-3 −/− ) hence have a severely disturbed spleen structure with the lack of the marginal zone and the red pulp, and thus they are incapable of providing the necessary microenvironment for B-cell maturation and T-cell-dependent (TD) immune reactions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we investigated the effect of the Nkx2-3 transcription factor (TF) genetic deficiency in autoimmune arthritis [ 26 ]. Nkx2-3 is a homeodomain TF which is crucial for the development of the spleen, and the expression and regulation of mucosal addressin cell adhesion molecule-1 (MADCAM-1) [ 28 , 29 ]. Nkx2-3 deficient mice (Nkx2-3 −/− ) hence have a severely disturbed spleen structure with the lack of the marginal zone and the red pulp, and thus they are incapable of providing the necessary microenvironment for B-cell maturation and T-cell-dependent (TD) immune reactions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…NKX2-3 plays crucial roles in many biologic processes, including cell proliferation and growth, metabolic process, immune and inflammatory response, and angiogenesis [ 29 , 30 ]. However, the abnormal expression of NKX2-3 is mostly seen in digestive system diseases, which has been considered as a gene related to inflammatory bowel disease and Crohn's disease [ 31 , 32 ]. A study has found that NKX2-3 could regulate the Wnt signaling pathway and then play a critical role in the pathogenesis of colorectal cancer and could be a new biomarker for clinical practice, including early diagnosis and subsequent therapy [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 As an important regulator, Nkx2-1 has been identified to influence rearranged during transfection (RET) expression in enteric neural cells, 23 whereas Nkx2-3 acts as a critical mediator promoting intestinal vascular patterning, [24][25][26] also influencing PP high-endothelial-venule (HEV) vascular addressin specification and gut lymphocyte homeostasis. 27,28 Lack of Nkx2-3 confers protection from colitis in a chemically induced mouse model. 29 Furthermore, Nkx2-3 + pericryptal mesenchymal cells may also contribute to the colonic epithelial stem cell niche, potentially influencing colonic cancer progression.…”
Section: Introductionmentioning
confidence: 99%